1979
DOI: 10.1182/blood.v54.1.13.bloodjournal54113
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival of increased-risk myeloma patients on combined triple- alkylating-agent therapy: a study of the CALGB

Abstract: Two hundred fifty-two previously untreated evaluable patients with multiple myeloma were entered into a study testing a regimen of three intravenous alkylating agents, melphalan, cyclophosphamide, and carmustine (BCNU), given in combination (BCMP) against a regimen employing oral melphalan (MP). Both regimens included a tapering course of prednisone. Objective responses based on the Myeloma Task Force criteria were significantly more frequent in the group receiving BCMP. Survival for the entire group of BCMP-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Multiple myeloma remains an incurable haematological malignancy characterized by various clinical manifestations such as hyperproteinaemia, renal dysfunction, bone lesions and immunodeficiency ( Oken, 1997; Bjorkstrand, 1996). Since the introduction of melphalan and prednisone (MP therapy) to improve the clinical response to multiple myeloma, large numbers of multi‐drug chemotherapies including vinca alkaloids, anthracyclines and nitrosoureas have been reported ( Case et al , 1977 ; Harley et al , 1979 ; Salmon et al , 1983 ; MacLennan et al , 1988 ). However, there has been little improvement in outcome during the past three decades ( Oken, 1997; Bjorkstrand, 1996).…”
mentioning
confidence: 99%
“…Multiple myeloma remains an incurable haematological malignancy characterized by various clinical manifestations such as hyperproteinaemia, renal dysfunction, bone lesions and immunodeficiency ( Oken, 1997; Bjorkstrand, 1996). Since the introduction of melphalan and prednisone (MP therapy) to improve the clinical response to multiple myeloma, large numbers of multi‐drug chemotherapies including vinca alkaloids, anthracyclines and nitrosoureas have been reported ( Case et al , 1977 ; Harley et al , 1979 ; Salmon et al , 1983 ; MacLennan et al , 1988 ). However, there has been little improvement in outcome during the past three decades ( Oken, 1997; Bjorkstrand, 1996).…”
mentioning
confidence: 99%
“…Combination chemotherapy has resulted in higher response rates than the standard melphalanprednisone in the treatment of multiple myeloma. At the time of planning the present study the higher response rates seemed to translate into prolonged survival times (3,7). There were, however, no data as to whether combination schedules also contained drugs that did not contribute to the result of the treatment or that were even harmful.…”
Section: Discussionmentioning
confidence: 87%
“…The report of Case et a1 (1) on their results of the application of the M-2 protocol was the first indication that an aggressive combination chemotherapy might be beneficial in the treatment of multiple myeloma. Some other trials on combination chemotherapy in myeloma were disappointing, and serious criticism appeared of the report of Case et al (2,3,10), cast doubt on the validity of their results and the role of vincristine in the combination. The total response rate (78%) in our multicentre trial is, however, in the same order as the reported response rates using M-2 in single-centre studies (87% and 78%, 1, ll), and the survival time among our patients from the initiation of the treatment is similar to that reported by Paccagnella et a1 (1 1) and Tirelli et a1 (12), and similar to the survial time of the patients of Case et a1 (1) from the diagnosis of myeloma.…”
Section: Discussionmentioning
confidence: 99%